Pengaruh Penggunaan Media Canva, Pembelajaran Berbasis Project dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Dasar Desain Grafis Peserta Didik Kelas X TKJ di SMK Sejahtera Surabaya - Ilmi, Evi Mavidhotul; Atiqoh, Atiqoh; Hartono, Hartono (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the influence of using Canva media, the Project Based Learning (PjBL) model, and the level of learning motivation on students’ learning outcomes in the subject of Basic Graphic Design. The background of this research lies in the importance of digital-based learning innovations that can enhance creativity, motivation, and learning achievement, particularly in vocational education. Canva is considered effective in supporting idea visualization, while PjBL provides opportunities for more collaborative and contextual learning. The study employed a quantitative approach with a quasi-experimental design, namely a pretest-posttest control group design. The sample consisted of 75 tenth-grade students of TKJ at SMK Sejahtera Surabaya, divided into three groups: PjBL-Canva, PjBL-Drawing Book, and Conventional-Canva. Research instruments included a learning achievement test (25 multiple-choice items) and a learning motivation questionnaire (19 items), both of which were tested for validity and reliability before data collection. The findings revealed an increase in the average score from 77.29 in the pretest to 79.44 in the posttest. The Wilcoxon signed-rank test yielded a significance value of p = 0.000, indicating a significant difference between pretest and posttest scores. Levene’s test for homogeneity (p > 0.05) confirmed homogeneous variances, allowing further parametric analysis. Motivation analysis showed that the Canva group tended to have high motivation, whereas the conventional group was relatively low. Hypothesis testing using the Paired Sample Test and two-way ANOVA demonstrated that Canva media and the PjBL model had a significant effect on learning outcomes, with a meaningful interaction between learning methods and motivation. The study concludes that integrating interactive digital media with project-based approaches is effective in improving students’ motivation and learning outcomes and is therefore recommended for vocational education.